Treatment of Class II division 1 Angle malocclusion with Extrabucal apparatus: a case report - Nascimento, Louyse Vaz do; de Sousa, Holga Joici Leão; Paiva Neto , Gerson de Oliveira; Oliveira, Nayhane Cristine da Silva de; Meira, Gabriela de Figueiredo; Santos, Bruna Ramos Meireles dos (Brazilian Journal of Case Reports, 2022)
Angle’s class II division 1 malocclusion is a condition where the maxillary first molar occludes in a mesial position in relation to the buccal groove of the mandibular first molar, altering the sagittal relationship between the jaws. The objective of the present study is to report a clinical case of treatment of Angle’s class II division 1 malocclusion in a 10-year-old female patient who was in the second transitional period of mixed dentition. The patient had mild to moderate crowding, due to lack of space to accommodate the lateral incisors and permanent canines in the maxillary arch. The proposed treatment was the use of the AEB for the distalization of the maxillary first molars, aiming at the correction of the class II molar relationship and, consequently, favoring the gain of space in the arch for the alignment of the crowded elements. According to the results presented at the end of the treatment, it was possible to observe the effectiveness of the headgear in the correction of class II molars and in the gain of arch space for the permanent incisors and canines.